Budaya Organisasi di Perguruan Tinggi: Studi di Sekolah Tinggi Ilmu Ekonomi (STIE) Abdi Bangsa Indonesia - Salfen Hasri (Jurnal Ilmu Pendidikan, 2016)
Organizational culture is a shared meaning of values, beliefs, traditions, and organizational philosophy which members of the organization own, so, the organization is different from the other organizations. Organizational culture that members feel is a quality, it is supported by the shared meaning based on the value of helping each other. The quality of culture is supported by all tangible and intangible organization elements. They are statements of vision and mission, organization value, artifacts, teaching-learning process, technology, the practice of management and accounting and training for English, Chinese, and Japanese skill.